1997
DOI: 10.4141/s96-018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal denitrification rates under corn (Zea mays L.) in two Quebec soils

Abstract: Nitrogen losses in soil through denitrification are important due to reduced agronomic effectiveness and environmental concerns with nitrous oxide emissions. Knowledge of denitrification may allow for management procedures to reduce these losses. Field experiments were conducted in 1991 and 1992 to investigate N fertilizer effects on denitrification under corn (Zea mays L.) on two soils of contrasting texture in southwestern Quebec. Soil core incubation with C2H2 was used to assess denitrification rates. Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…In general, seasonal patterns of DEA in the field show decreasing rates during the summer months due to low soil moisture (Limmer and Steele 1982;Tiedje et al 1989) and increasing rates after spring thaw (Christensen and Tiedje 1990) and in fall when soil moisture increases (Parsons et al 1991;Liang and MacKenzie 1997). Our data demonstrated a similar seasonal pattern for DEA measured at nine different temperatures.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In general, seasonal patterns of DEA in the field show decreasing rates during the summer months due to low soil moisture (Limmer and Steele 1982;Tiedje et al 1989) and increasing rates after spring thaw (Christensen and Tiedje 1990) and in fall when soil moisture increases (Parsons et al 1991;Liang and MacKenzie 1997). Our data demonstrated a similar seasonal pattern for DEA measured at nine different temperatures.…”
Section: Discussionsupporting
confidence: 76%
“…These divergent results could be due to the capacity of denitrifiers to adapt to their environmental temperature or to temperature-induced shifts in the structure of the soil denitrifier community (Kaplan et al 1977;King and Nedwell 1984). Constant emissions of N 2 O measured during the cold season in Quebec strongly suggest that denitrification is important at low temperatures (van Bochove et al 1996;Liang and MacKenzie 1997). Furthermore, N 2 O-N losses during winter and spring melt (under snow cover) may constitute a significant part of the annual N budget as observed by van Bochove et al (1996) in a study on an agricultural soil.…”
mentioning
confidence: 99%
“…Malhi and Nyborg (1986) reported loss of 44 kg N ha -1 under conditions prevailing in early spring for soils of north-central Alberta. Liang and MacKenzie (1997) found that for a sandy clay loam in the St. Lawrence lowlands losses of NO 3 -by denitrification were related to soil moisture in April and May. Chantigny et al (1999) reported that denitrification rates were inversely related to air-filled porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Release of N 2 O, a greenhouse gas that depletes ozone layer, via denitrification was also reported for soils receiving excess fertiliser N (Liang and MacKenzie 1997). The presence of NO 3 -in soils after harvest and in early spring was associated with a risk of both leaching (Chichester 1977;Malhi and Nyborg 1986;Liang et al 1991) and denitrification (Goodroad and Keeney 1984;Liang et al 1991;Liang et MacKenzie 1997). Therefore, the reduction of the risk of air and water pollution from agricultural soils implies that the soil residual NO 3 content in fall and early spring should be kept at a minimum.…”
mentioning
confidence: 90%
“…The experimental design, method and timing of fertilizer N application, and the management of field plots have been reported previously (Liang and MacKenzie 1997). Corn was grown continuously on the Chicot soil since 1984, and on the Ste.…”
mentioning
confidence: 99%